Natsteel Services (Malaysia) Sdn Bhd / Siti Nur Hidayah Zaini - Zaini, Siti Nur Hidayah (Faculty of Business and Management, 2023)
For the past six months, I have had the wonderful chance to train and get job experience at Easteel Services (Malaysia) Pte. Ltd. I'm Siti Nur Hidayah binti Zaini, a senior at UiTM Kampus Bandaraya Melaka studying Office Systems Management (Hons). One of NatSteel's fully owned subsidiaries, Easteel Services (Malaysia) Pte. Ltd., offers prefabrication services and products for wire mesh products, mainly for companies in the construction sector. At ESM, all products are created with a commitment to quality and in accordance with the specifications supplied by clients. There are 200 employees at this company, including regular staff and interns of different racial and age groups. Regarding my internship training, I can say that it was a wonderful and instructive moment for me throughout my internship term. I was assigned to the production team as a production admin, where I picked up a lot of new skills in administrative tasks including entering data into various documents like key in MESH output in the provided Excel, uploading data to SAP systems, and recording data. Overall, it is really enlightening and practical. The SWOT analysis, which examines the company's internal and external factors, is used in this study. To help determine the company's production performance, this analysis is used. This study also focuses on the advantages and disadvantages I encountered while finishing my internship at the organization.